Influence of physical exercise on serum digoxin concentration and heart rate in patients with atrial fibrillation. - Bøtker, H E (1991)
Heart rate and serum digoxin concentration in eight patients with atrial fibrillation were studied at rest and during exercise when initial serum digoxin concentrations were zero and at low and high therapeutic values. Eight patients with ischemic heart disease and in sinus rhythm were studied for comparison. Though the serum digoxin concentration decreased significantly during exercise, the absolute reduction in heart rate was the same at rest and during exercise in patients with atrial fibrillation. Compared with the control patients in sinus rhythm, the heart rate in patients with atrial fibrillation was not adequately controlled during exercise by any serum digoxin concentration tested despite a reduction in heart rate with increasing digoxin concentration. The effects of digoxin on heart rate regulation in atrial fibrillation are complex and include direct effects on the myocardium as well as indirect effects mediated by modulation of the autonomic nervous system; the present results indicate that the drug is not displaced from the target organs by decreasing serum concentrations during exercise. In atrial fibrillation, because the demands on the filter function of the atrioventricular node are highly unphysiological, the effect of digoxin on heart rate during exercise is not adequate.